Design Elements and Illuminations in Nigerian “Market Literature” in Arabic and ʿAjamī - Dobronravin, Nikolai (Islamic Africa, 2017)
“Market literature” in Arabic and ʿAjamī is a particular variety of West African Islamic book culture, which is especially strong in northern Nigerian states. Arabic-script “Nithography” (by analogy to Nollywood, the modern Nigerian film industry) represents a unique phenomenon, although it is reminiscent of the nineteenth-century Islamic lithography in the Middle East. Nigerian “market literature” in Arabic and ʿAjamī has mostly followed the pre-colonial manuscript tradition of Central Sudanic Africa, including writing styles, colophons and glosses. In contrast to Middle Eastern book culture, Nigerian typeset printing largely preceded the era of offset. The innovative elements of offset book design in Nigeria and further perspectives of “Nithography” in Arabic and ʿAjamī are discussed.